New Insights from Metabolomics in Pediatric Renal Diseases - Simona Riccio; Maria Sole Valentino; Antonio Paride Passaro; Marica Izzo; Stefano Guarino; Emanuele Miraglia del Giudice; Pierluigi Marzuillo; Anna Di Sessa (Children, 2022)
Renal diseases in childhood form a spectrum of different conditions with potential long-term consequences. Given that, a great effort has been made by researchers to identify candidate biomarkers that are able to influence diagnosis and prognosis, in particular by using omics techniques (e.g., metabolomics, lipidomics, genomics, and transcriptomics). Over the past decades, metabolomics has added a promising number of ‘new’ biomarkers to the ‘old’ group through better physiopathological knowledge, paving the way for insightful perspectives on the management of different renal diseases. We aimed to summarize the most recent omics evidence in the main renal pediatric diseases (including acute renal injury, kidney transplantation, chronic kidney disease, renal dysplasia, vesicoureteral reflux, and lithiasis) in this narrative review.